2009
DOI: 10.1016/j.apmr.2008.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surface Type, Wheelchair Weight, and Axle Position on Wheelchair Propulsion by Novice Older Adults

Abstract: Objective To examine the impact of surface type, wheelchair weight, and rear axle position on older adult propulsion biomechanics. Design Crossover trial. Setting Biomechanics laboratory. Participants Convenience sample of 53 ambulatory older adults with minimal wheelchair experience (65−87y); men = 20, women = 33. Intervention Participants propelled 4 different wheelchair configurations over 4 surfaces; tile, low carpet, high carpet, and an 8% grade ramp (surface, chair order randomized). Chair config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 19 publications
3
79
0
8
Order By: Relevance
“…Cowan et al concluded that the greatest reductions in the resultant peak force would be obtained with the lightest possible wheelchair [19]. To our knowledge, no studies have been carried out on satisfaction with wheelchair accessories.…”
Section: Marchiori Et Al Manual Wheelchair Satisfactionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cowan et al concluded that the greatest reductions in the resultant peak force would be obtained with the lightest possible wheelchair [19]. To our knowledge, no studies have been carried out on satisfaction with wheelchair accessories.…”
Section: Marchiori Et Al Manual Wheelchair Satisfactionmentioning
confidence: 92%
“…affects self-selected velocity, peak resultant force, and peak tangential force and that the addition of 9 kg reduces self-selected velocity and increases peak forces on each surface [19]. Cowan et al concluded that the greatest reductions in the resultant peak force would be obtained with the lightest possible wheelchair [19].…”
Section: Marchiori Et Al Manual Wheelchair Satisfactionmentioning
confidence: 99%
“…It has been reported that propulsion velocity decreases with an increase in rolling resistance. 20 That is likely to have been a factor in the relatively low self-selected speed of our participants.…”
Section: Study Limitationsmentioning
confidence: 99%
“…contact angle, release angle) and temporal (i.e. push time, cadence) variables are influenced by propulsion technique and differences in upper extremity impairment (e.g., Newsam et al, 1996;Finley et al, 2004;Mulroy et al, 2004), training (e.g., Rodgers et al, 2001;Rice et al, 2010;Richter et al, 2011) and terrain (e.g., Newsam et al, 1996;Richter et al, 2007;Chow et al, 2009;Cowan et al, 2009). The wheelchair propulsion technique analyzed in this study was derived from representative spatiotemporal values (e.g., Richter, 2001;PVACSCM, 2005;Lin et al, 2009), but other techniques exist.…”
Section: Limitations and Future Workmentioning
confidence: 99%